2018
DOI: 10.1158/1538-7445.am2018-923
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 923: The cBioPortal for Cancer Genomics: An intuitive open-source platform for exploration, analysis and visualization of cancer genomics data

Abstract: The cBioPortal for Cancer Genomics is an open source software platform that enables interactive, exploratory analysis of large-scale cancer genomics data sets. It integrates genomic and clinical data, and provides a suite of visualization and analysis options, including cohort and patient-level visualization, mutation visualization, survival analysis, alteration enrichment analysis, and network analysis. The user interface is user-friendly, responsive, and makes genomic data easily accessible to scientists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…TUBB6 mutation analysis was produced by COSMIC database (Tate et al, 2019) and characterized in a pie chart. The frequency of TUBB6 mutations in GBM was tested by cBioPortal (Gao et al, 2018).…”
Section: Identification Of Prognostic Demfgs and Construction Of The mentioning
confidence: 99%
“…TUBB6 mutation analysis was produced by COSMIC database (Tate et al, 2019) and characterized in a pie chart. The frequency of TUBB6 mutations in GBM was tested by cBioPortal (Gao et al, 2018).…”
Section: Identification Of Prognostic Demfgs and Construction Of The mentioning
confidence: 99%
“…27 Therefore, we analyzed the frequency of mutations in the genes encoding receptors and ligands from the Wnt, Notch, Hedgehog, and TGFb pathways, using the mutational data from cBioPortal as an interface for TCGA data. 28 We found that mutational burden, even in survival-significant receptors or ligands, such as FZD2, WNT7A, NOTCH2, ACVRL1, and BMP2, was low, with mutations present at very low frequency compared to the frequency in commonly mutated genes, such as TP53, KRAS, or PTEN (Fig. S1).…”
Section: Enrichment Of Developmental Signaling Pathwaysmentioning
confidence: 87%
“…To validate our pipeline, we used gene fusions covering the genes ERG , ETV1 , ETV4 , and FLI1 reported by the TCGA consortium for the TCGA_PRAD cohort as a reference. The annotated data from the TCGA consortium was provided by the cBioPortal for Cancer Genomics database [ 31 ] in the Prostate Adenocarcinoma study (TCGA, Cell 2015). We compared the samples carrying an ERG -fusion as published by the TCGA consortium with those for which we detected an ERG -fusion in TCGA_PRAD with the Arriba pipeline one-to-one and created contingency tables of the results.…”
Section: Methodsmentioning
confidence: 99%